Re-Recruitment: An Essential Aspect of Human Experience - Thom Mayer; David Fessell; Amy Young (Patient Experience Journal)
Healthcare staffing is a major issue facing leaders at all levels and is affected by turnover rates in ``The Great Resignation,'' as well as the issue of burnout, moral injury, and turnover. In seeking to deal with defining and making human experience as reality, these factors affect every level, from patient experience to workforce experience to community experience, all of which are related to not just adequate staffing and preventing turnover but doing so with our highest performing ``A Team'' members. Using the tool of re-recruitment of these high-level professionals and team members can be critical to retaining talent, while providing an improved human experience at every level of the organization. This entails continuously re-recruiting A Team members, coaching and mentoring B Team members to re-join the A Team through specific disciplines, and considering whether C Team members are able to change. Specific examples and tools are demonstrated.